Effect of Culturally Responsive Teaching through The Garut Dodol Context on Mathematical Problem-Solving Ability - Serly Agustina Hendarman; Edi Hidayat; Depi Setialesmana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The low level of students’ mathematical problem solving ability remains a significant challenge in mathematics education, particularly when instructional processes are abstract and fail to connect mathematical concepts with cultural contexts relevant to students’ daily lives. In this regard, the traditional food Dodol Garut is utilized as an ethnomathematical context, as its production process involves sequential and interrelated stages that represent the concept of composite functions and align with students’ real-life experiences. This study aims to examine: (1) the effect of the Culturally Responsive Teaching (CRT) approach through the context of Dodol Garut on students’ mathematical problem solving ability, and (2) the percentage distribution of students’ mathematical problem solving ability across high, medium, and low categories after the implementation of the CRT approach.This research employed a quasi-experimental method with a Posttest-Only Control Group Design. The population consisted of eleventh-grade students at SMAN 18 Garut. Using cluster random sampling, two classes were selected: class XI-4 as the experimental group and class XI-5 as the control group. The research instrument was a mathematical problem-solving test based on the indicators proposed by Krulik and Rudnick, which had been validated in terms of content validity and reliability. Data were analyzed using the Shapiro–Wilk normality test, the Mann–Whitney U test, and effect size calculation. The results indicated a Z value of 2.149 with an effect size (η²) of 0.0624, which falls into the medium category. Descriptively, 67.57% of students were categorized as high, 29.73% as medium, and 2.70% as low in their mathematical problem solving ability. The novelty of this study lies in the integration of traditional food context within CRT-based mathematics learning.